Involvement of trigeminal neuralgia in type 2 diabetes - Tomislav Badel; Miroslav Hrelja; Jelena Bošnjak; Dijana Zadravec; Matea Prenc; Mia Smoljan (Journal of Dental Problems and Solutions - Peertechz Publications, 2023)
The aim of this paper is to describe orofacial neuralgic pain related to diabetes mellitus pathology with a clinical report of a female patient who suffered from diabetic polyneuropathy. A 61-year-old female patient was treated neurologically and dentally due to suspicions of Trigeminal Neuralgia (TN) and disorders of the temporomandibular joint. Recent symptoms were burning and heat, electric shock sensation related to the right side of the face and particularly the second right premolar tooth. The patient had received regular insulin therapy (type 2 diabetes mellitus) for the last 10 years and was diagnosed with diabetic polyneuropathy with a higher value of glycosylated hemoglobin HbA1c (59 mmol/mol). The psychological evaluation showed an elevated anxiety level according to Spielberger's State-Trait Anxiety Inventory. The most common neurogenic complication of type 2 DM is diabetic polyneuropathy. The functional status of the trigeminal reflex pathways was reflected through the blink reflex. There were a few existing reports of the relationship between diabetes mellitus and TN- related orofacial pain, which is discussed in this paper.